Lower adherence to a prudent dietary pattern is associated with earlier age at menarche in adolescents from the Growth and Obesity Chilean Cohort Study - Martínez-Arroyo, Angela; Cantor, Erika; Fisberg, Regina Mara; Corvalán, Camila (Frontiers in Public Health, 2023)
Introduction Early menarche is associated with obesity, and metabolic and mental health risks, among other diseases. Thus, it is relevant to identify modifiable risk factors of early menarche. Some nutrients and foods have been linked to pubertal timing, but how menarche relates to overall dietary patterns is unclear. Methods The aim of this study was to analyze the association between dietary patterns and age at menarche in a prospective cohort of Chilean girls from low and middle-income families. We conducted a survival analysis of 215 girls (median = 12.7 years, IQR = 12.2–13.2) from the Growth and Obesity Cohort Study (GOCS) who had been followed prospectively since 4 years of age (2006). Age at menarche and anthropometric measurements were recorded every 6 months since 7 years of age while diet (24-hour dietary recall) was collected for 11 years. Dietary patterns were obtained from exploratory factor analysis. Accelerated Failure Time models adjusted for potential confounding variables were used to study the association between dietary patterns and age at menarche. Results Girls' median age at menarche was 12.7 years. Three dietary patterns were identified: “Breakfast/Light Dinner,” “Prudent” and “Snacking” which explained 19.5% of the diet variation. Girls in the lowest tertile of the “Prudent” pattern had menarche 3 months earlier than girls in the highest tertile (β: 0.022; 95% CI: 0.003; 0.041). “Breakfast/Light Dinner” and “Snacking” patterns were not associated with age at menarche. Conclusion Our results suggest that healthier dietary patterns during puberty might be associated with menarche timing. Nevertheless, further studies are required to confirm this result and to clarify the association between diet and puberty.